Effectiveness of Blended Learning in the Academic Performance of Selected Tourism Students: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Blended Learning is a type of learning approach that combines the use of traditional face-to-face classes and online-based teachings. Briones (2020) states that the Philippines has been practising Blended Learning for decades, even before the pandemic. Several universities, colleges, and schools in the country have been giving online modules and tests to their students as a part of their curriculum. Lyceum of the Philippines Laguna used Blended Learning even before the pandemic. Catapang (2018) stated that the Lyceum of the Philippines Laguna Campus is implementing an online LMS as a part of its curriculum. It has received positive feedback from the students and teaching faculty as it improves student engagement and allows better connections to one another. Blended Learning is effective for the student’s academic performance because it promotes flexibility, ownership, self-improvement and a better learning experience. Despite these benefits, there are still disadvantages in Blended Learning, such as a lack of connection and technology and difficulty in shifting from traditional face-to-face classes to online classes that may hinder the student’s academic growth.